Policies and Strategies for Handling Uninhabitable Houses (RTLH) in Malang City - suprianto, supri (Badan Perencanaan Pembangunan Kota Malang, 2025)
Inadequate housing (RTLH) is one of the main challenges in urban governance, especially in areas with high poverty rates. Malang City, as a major city in East Java, is facing RTLH issues that require strategic interventions and effective policies. Based on data from SATUDATA Malang City, the number of RTLH has decreased from 1,471 units in 2022 to 1,013 units in 2024. This decrease was supported by a budget allocation of IDR 2 billion from the Malang City Government in 2024 which was used to rehabilitate 100 RTLH units using the roof, floor and wall repair (aladin) method. In addition, the involvement of various stakeholders, such as Baznas Malang City and the private sector, also contributed to the efforts to improve housing for low-income people. This article aims to analyze the policies that have been implemented, evaluate the effectiveness of the RTLH rehabilitation program, and provide policy recommendations that are more optimal in accelerating RTLH settlement in Malang City. Using a quantitative descriptive analysis method, this research processes data from various official sources to provide a comprehensive picture of the development of RTLH and strategies that can be implemented to improve the quality of housing in Malang City in a sustainable manner